A diverse group of underappreciated zygnematophytes deserves in-depth exploration. Issue 1 (31st December 2022) - Busch, Anna; Hess, Sebastian
ABSTRACT: The conjugating green algae (Zygnematophyceae) are the closest relatives of land plants and hence are of great evolutionary interest. Besides the popular placoderm desmids and the filamentous species, there is an underappreciated diversity of unicellular zygnematophytes with a much "simpler" morphology and smooth cell walls – traditionally referred to as "saccoderm desmids". These saccoderm desmids have a broad geographic distribution and are ecologically diverse. Many species inhabit terrestrial habitats such as dead wood, rock surfaces and glacial ice. Furthermore, several of the saccoderm genera have turned out to be highly polyphyletic and are typically poorly captured by environmental sequencing approaches. One of these genera is Mesotaenium Nägeli, with ~70 described species and infraspecific taxa united only by a relatively simple (plate- or ribbon-like) chloroplast structure. Here, we shed some light on these inconspicuous yet important members of the algal flora and present an updated rbc L gene phylogeny of the conjugating green algae, including several new lineages of Mesotaenium -like zygnematophytes. We depict the subtle morphological differences among these lineages and discuss our updated phylogeny in the light of ecology and cell biology. In addition, we review published knowledge on photoprotective strategies of zygnematophytes, the latest insights into their evolutionary innovations, and address some technical challenges in exploring this elusive group of microalgae. Some new observations of saccoderm desmids in undersampled habitats and of their microbial associates (e.g., parasites) point to interesting avenues for future research.